1996
DOI: 10.1107/s0907444995007293
|View full text |Cite
|
Sign up to set email alerts
|

X-ray structure of the signal transduction protein from Escherichia coli at 1.9 Å

Abstract: The structure of the bacterial signal transduction protein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 24 publications
2
78
0
2
Order By: Relevance
“…X-ray crystallographic analysis of the homotrimeric PII and GlnK proteins from E. coli reveals a similar structural core, although the conformation of the apical T-loop can alter significantly (43)(44)(45). The T-loop region of Ec PII is necessary for interaction with ATase, UTase, and NtrB and includes Tyr-51, the site of uridylylation (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…X-ray crystallographic analysis of the homotrimeric PII and GlnK proteins from E. coli reveals a similar structural core, although the conformation of the apical T-loop can alter significantly (43)(44)(45). The T-loop region of Ec PII is necessary for interaction with ATase, UTase, and NtrB and includes Tyr-51, the site of uridylylation (31,33).…”
Section: Discussionmentioning
confidence: 99%
“…This led to further studies by Mangum et al on the role of P II in GS regulation (26) and studies by Garcia and Rhee (27) showing that the uridylylation and deuridylylation of P II is catalyzed by the same uridylyltransferase (UTase). Subsequently, Adler et al (28) obtained a homogeneous preparation of P II and showed that it is a protein of about M r 44,000, which was later shown by other workers to be a trimer (29). In continuing studies, Adler and Purich showed that uridylylation of P II involves covalent attachment of a uridylyl group from UTP to a particular tyrosine residue in each subunit (Reaction 3, where n ϭ 1-3) and that deuridylylation of the uridylylated P II is a hydrolytic process (Reaction 4).…”
Section: Purification Of the P II Regulatory Protein And The Demonstrmentioning
confidence: 99%
“…Arabic numerals indicate gene designations relative to whole genome analyses (9,14). The predicted T-loop is indicated (39,40). * indicates the tyrosine reside which is the conserved site of uridylylation in Bacteria.…”
Section: Post-transcriptional Regulation and The Novel Glnb Homologuementioning
confidence: 99%